Bone marrow tolerance during postoperative chemotherapy in colorectal carcinomas - Newman, Neil B.; Moss, Rebecca A.; Maloney-Patel, Nell; Donohue, Kristen; Brown, Teresa V.; Nissenblatt, Michael J.; Lu, Shou-En; Jabbour, Salma K. (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Background: This study seeks to quantify and compare bone marrow tolerance during postoperative chemotherapy therapy between rectal cancer vs. colon cancer patients. During rectal cancer treatment, patients receive neoadjuvant chemoradiation (CRT) irradiation which can exacerbate the hematologic toxicity (HT) via incidental irradiation of the pelvic bone marrow (PBM) during myelosuppressive postoperative chemotherapy. In contrast, colon cancer patients receive the same postoperative myelosuppressive chemotherapy but do not routinely receive preoperative chemoradiation therapy. This comparison will help elucidate the lasting myelosuppressive effects of incidental pelvic bone marrow (PBM) irradiation on rectal cancer patients during neoadjuvant preoperative chemoradiation therapy. Methods: Rectal cancer patients treated with preoperative CRT followed by postoperative 5-Fluorouracil and oxaliplatin (OxF) chemotherapy (n=35) were compared to colon cancer patients who received only postoperative OxF chemotherapy (n=42). End points were ≥ grade 3 hematologic toxicity (HT3) or hematologic event (HE) defined as ≥ grade 2 HT and a dose reduction in OxF. Wilcoxon rank sum test tested continuous variables and Chi-squared test measured differences in categorical variables. HT3 and HE probability during postoperative chemotherapy was estimated with Kaplan-Meier curves and Cox regression analysis. Results: During OxF chemotherapy, 40.0% (n=14) of rectal cancer patients experienced HT3 compared to 26.1% (n=11) of colon cancer patients (P=0.4). HE was experienced by 48% (n=17) of rectal cancer patients compared to 36% (n=15) of colon cancer patients (P=0.36). Rectal cancer patients were likelier to experience HT3 on multivariable cox regression analysis, controlling for several clinical covariates, with a hazard ratio (HR) of 2.49, [(95% CI: 1.02–6.02), P=0.045] than colon cancer patients. While rectal cancer patients were more likely to experience HE than colon cancer patients on multivariable Cox regression analysis with a HR of 1.8 (95% CI: 0.95–3.75), this only trended in statistical significance, P=0.07. Conclusions: Rectal cancer patients are more likely than colon cancer patients to experience hematologic toxicities impacting the tolerance of standard of care chemotherapeutics during adjuvant therapy. Focused PBM sparing during radiation therapy for rectal cancer patients may improve tolerance of myelosuppressive chemotherapeutic agents delivered in the postoperative setting.